Implementing a multimodal online program for very young learners of Russian: Educators' perspective - Kayumova, Albina; Sadykova, Gulnara (Universitas Pendidikan Indonesia, 2019)
CALL and MALL learning programs have been introduced by preschool teachers into their language classrooms (Sadykova, Kayumova, Khalitova, Gimaletdinova, 2017; Segers Verhoeven, 2003), despite reports saying that some of these programs have little educational value (Kazanci Okan, 2009). This exploratory mixed-methods study aims at examining how Russian language kindergarten and preschool teachers integrate resources of a Russian language online school Live Fairytalesâ„¢ (Zhivye skazki, 2017) and what design elements of this multimodal digital resource they find conducive or impediment to successful language acquisition by young learners. The data come from the reports of six teachers and survey responses of 18 educators who described and reflected on their experiences integrating resources of the Russian language online school. The data show that teachers made productive use of the digital resource by utilizing its multimodal presentation of the content, integrating interactive activities mostly in a whole-class format, and creating an engaging and enjoyable learning environment of play. Visual representation of material was reported to be the most valuable and necessary for accompanying audio input, introducing or practicing vocabulary, supporting listening comprehension, and overall motivating very young learners to stay on task. This study extends our understanding of what early childhood educators expect from quality digital resources and how they integrate them into educational programs that support language acquisition of bilingual and multilingual preschool children.Â